Regulation of collagenases matrix metalloproteinases with CTCF/YB-1 transcription factors in human malignant melanoma cancer in vitro - Ibrahim, Wisam Nabeel (Kulliyah of Allied Health Sciences, International Islamic University Malaysia, 2018)
The invasiveness of malignant melanoma is mainly attributed to the enzymatic destruction of the extracellular matrix and basement membrane components by a group of enzymes known as matrix metalloproteinases (MMPs). The expression of these proteinases is mainly regulated at the transcriptional level; therefore, high expression of MMPs is manly attributed to different transcription factors which enhance or inhibit the promoter activity of MMPs genes. Among these factors, YB-1 and CTCF proteins are transcription factors in which CTCF is mainly a tumour suppressor protein; while YB-1 is an oncogenic factor and a prognostic indicator in a wide range of tumours that regulates most of the cancer processes such as proliferation, invasion and metastasis by regulating the expression of genes related to those processes. However; the expression of these transcription factors and their potential effect on the expression of collagenases MMPs in malignant melanoma cells are not yet confirmed. Therefore, this study was conducted to determine the expression of collagenases MMPs (MMP1, MMP8 and MMP13), YB-1 and CTCF transcription factors in A375 melanoma cancer cells. In addition, the stromal effect of normal skin fibroblasts on the expression of collagenases and proliferation in A375 cell was determined. The results of this experiment demonstrated an increase in the expression of YB-1, MMP8 and MMP13 in A375 cells. Thereafter, this was followed by the establishment of YB-1 silenced strain of A375 cells using a silencing short hairpin RNA (shRNA) construct. The effect of YB-1 knockdown on the expression of collagenases MMPs was determined using reverse transcription PCR and Western blotting. In addition, the antiproliferative effect was determined using flow-cytometry, colorimetric MTT assay and cell counting; while the anti-invasive properties were determined using wound healing assay. The results of this experiment elucidated that YB-1 protein regulates the expression of MMP13, cell cycle progression, cell proliferation and cell migration of A375 cancer cells in vitro. Therefore, the direct interaction between YB-1 protein and the AP-1 promoter sequence of MMP13 was evaluated using Chromatin Immunoprecipitation assay (ChIP). The ChIP analysis has confirmed no interaction between YB-1 protein and the AP-1 promoter sequence. Finally, these experiments demonstrated YB-1, MMP8 and MMP13 were highly expressed in the A375 cancer cells. The stromal cells were found to promote A375 cell proliferation and enhance the expression of MMP1. In addition, YB-1 silencing was significantly associated with reduced expression of MMP13 enzyme, reduction in cancer cell proliferation in a cell cycle specific manner and anti-invasive properties. Therefore, YB-1, MMP13 and stromal cells are considered as promising elements that might help as a potential target in the treatment of melanoma tumour due to their roles in the processes of invasion, migration and proliferation. Further experiments are needed to demonstrate novel protein partners of YB-1 and novel binding sites within gene promoter region of MMP13 with determination of the involved signalling pathways.